Advances in Reconfigurable Mechanisms and Robots II - Ding, Xilun; Kong, Xianwen; Dai, Jian S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents the most recent advances in the research and applications of reconfigurable mechanisms and robots. It collects 93 independently reviewed papers presented at the Third ASME/IFToMM International Conference on Reconfigurable Mechanisms and Robots (ReMAR 2015) held in Beijing, China, 20-22 July 2015. The conference papers are organized into seven parts to cover the reconfiguration theory, topology, kinematics and design of reconfigurable mechanisms including reconfigurable parallel mechanisms. The most recent results on reconfigurable robots are presented including their analysis, design, simulation and control. Bio-inspired mechanisms are also explored in the challenging fields of rehabilitation and minimally invasive surgery. This book further addresses deployable mechanisms and origami-inspired mechanisms and showcases a wide range of successful applications of reconfigurable mechanisms and robots. Advances in Reconfigurable Mechanisms and Robots II should be of interest for researchers, engineers and postgraduate students in mechanical engineering, electrical engineering, computer science and mathematics. .
Chirikjian -- Singularity Analysis of a High-Speed Parallel Robot with Schönflies Motion, by Fugui Xie, Xin-Jun Liu and Zubing Min -- Multi-objective Design Optimization of a Parallel Schönflies-motion Robot, by Guanglei Wu, Shaoping Bai and Preben Hjørnet -- Mechanism Synthesis and Workspace Analysis of a Spraying Robot for Airfoil, by Lizhong Zhu, Liping Wang and Jingshan Zhao -- A Novel Docking Mechanism Design and Dynamic Performance Analysis of Self-reconfigurable Modular Robot, by Xiaofeng Wang, Minglu Zhang and Weimin Ge -- Conceptual Design and Kinematic Analysis of the Diamobot: A Homogeneous Modular Robot, by Longhai Zhao, Hao Wang, Tianwei Lin, Genliang Chen and Lingyu Kong -- Design and Development on a Reconfigurable Modular Joint of the Robot Arm, by Jiaming Deng, Pengcheng Wang, Qingmei Meng, Huiping Shen, Jian Chen and Minzhou Luo -- A New Approach to Identify Link Errors and Kinematic Pair Errors of SCARA Robot, by Zhi Wang, Delun Wang, Huimin Dong and Shudong Yu -- Structural Topology Optimization for a Robot Upper Arm Based on SIMP Method, by Yunfei Bai, Ming Cong and Yongyao Li -- Intelligent Service Reconfiguration for Home Robots, by Tsung-Hsien Yang and Wei-Po Lee -- Design and Simulation of Metamorphic Moving Mechanism of Insulator Inspection Robot, by S. J. Li, Q. Yang, M. Geng and H.G. Wang -- Compliance analysis and synthesis of a serial manipulator with redundant DOFs used in Tokamak, by Jue Yu, Yong Zhao, Hao Wang, Li Wang and Xinmin Lai -- A Modular Liquid Sample Handling Robot for High-throughput Fourier Transform Infrared Spectroscopy, by Jichun Li, Volha Shapaval, Achim Kohler, Robert Talintyre, Jürgen Schmitt, Richard Stone, Andrew J Gallant and Dagou A Zeze -- Reconfigurable Industrial Robots - an integrated approach to design the joint and linkmodules and configure the robot manipulator, by Anna Valente -- M2 Gripper: Extending the Dexterity of a Simple, Underactuated Gripper, by Raymond R. Ma, Adam Spiers and Aaron M. Dollar -- Design and Analysis of a Circular-Orbit Underconstrained Cable Parallel Robot, by Sen Qian, Bin Zi and Xue Han -- Kinematics and energy minimization approach for continuum robot, by Qiang Lu and Bin He -- Par.
Keywords: Control engineering; Robotics; Automation; Machinery; Manufactures; Control, Robotics, Automation; Machinery and Machine Elements; Machines, Tools, Processes